Syntheses, characterizations, thermal and photophysical properties of cyclophosphazenes containing adamantane units - Un, Ilker; Ibisoglu, Hanife; Un, Sule Sahin; Cosut, Bunyemin; Kilic, Adem (Elsevier Science Sa, 2013)
In this study, phenoxy-adamantane substituted cyclophosphazene compounds (5-8) were synthesized in three steps. Firstly; adamantane derivatives (1 and 2) containing alkyne groups were prepared. Secondly; 2,2,4,4,6,6-hexzakis-(2'-azido-1'-ethoxy)-cyclotriphosphazatriene (3) and 2,2,4,4,6,6,8,8-octakis-(2'-azido-1'-ethoxy)-cyclotetraphosphazatetraene (4) were synthesized from the nucleophilic substitutions of 2-azido-1-ethanol with trimer (N3P3Cl6) and tetramer (N4P4Cl8) in THF respectively. Thirdly; cyclophosphazenes containing adamantane units (5-8) were obtained by the Cu(I) catalyzed click reactions of cyclophosphazenes (3 and 4) with compounds 1 and 2. The structural investigations of newly synthesized compounds 1-8 were evaluated by elemental analysis and FT-IR (ATR), mass spectrometry, H-1, C-13, H-1-C-13 HSQC (for 6) and P-31 NMR (for 3-8) spectroscopies. Compound 1-8 were also reported for the first time. The thermal and photophysical properties of 5-8 were investigated. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Cyclophosphazene; Adamantane; Thermal stability; Fluorescence; NMR